Elimination of lymphatic filariasis: adapting to reach the end game - Lammie, Patrick (Henry Stewart Talks, 2021)
Lymphatic filariasis, Wuchereria bancrofti, Transmission of LF, Diagnostic tools for LF, Drugs to treat LF, LF elimination strategy, Conducting mass drug administration, How do we measure progress and success?, What are the challenges facing the program?